Parent-Child Dyadic Coping and Quality of Life in Chronically Diseased Children - Nap-van der Vlist, Merel M.; van der Wal, Reine C.; Grosfeld, Eva; van de Putte, Elise M.; Dalmeijer, Geertje W.; Grootenhuis, Martha A.; van der Ent, Cornelis K.; van den Heuvel-Eibrink, Marry M.; Swart, Joost F.; Bodenmann, Guy; Finkenauer, Catrin; Nijhof, Sanne L. (Frontiers in Psychology, 2021)
Different forms of dyadic coping are associated with positive outcomes in partner relationships, yet little is known about dyadic coping in parent-child relationships. The current research explored the association between parent-child dyadic coping and children’s quality of life in children with a chronic disease (i.e., cystic fibrosis, autoimmune diseases and children post-cancer treatment). In a sample of 105 parent-child dyads, self-reported forms of dyadic coping (i.e., stress communication, problem-oriented, emotion-oriented, and negative dyadic coping) and children’s quality of life were assessed. Children reported more stress communication and negative dyadic coping than their parents, while parents reported more problem-oriented dyadic coping and emotion-oriented dyadic coping than their children. More stress communication of the child was associated with more emotion-oriented dyadic coping and less negative dyadic coping of the parent. More negative dyadic coping of the child was associated with less stress communication, problem-oriented dyadic coping and emotion-oriented dyadic coping of the parent. Additionally, both children’s and parents’ negative dyadic coping were associated with lower self-reported pediatric quality of life and parents’ emotion-oriented dyadic coping was associated with higher pediatric quality of life. These findings emphasize that children and their parents mutually influence each other and that dyadic coping is associated with children’s quality of life. Theoretical and practical implications are discussed.